The Role of Teachers in Implementing Environmentally Based Learning Media through Animated Videos in Elementary Schools - Farisatma; Yusnan, Muhammad; Jannah, Nur; Krisnawati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2024)
Environmental-based learning media through animated videos in Elementary Schools is an effective innovation in improving students' understanding of the material being taught. By utilizing animation technology, abstract concepts in learning can be presented more interestingly and easily understood. The purpose of the study was to determine the role of teachers in implementing environmental-based learning media through animated videos. This study is a qualitative study with a descriptive approach that aims to understand and describe the role of teachers in implementing environmental-based learning media through animated videos. The results of the study show that teachers have an important role in implementing environmental-based learning media through animated videos at Kaobula 2 Elementary School. As a media designer, teachers must adjust and select videos that are relevant to the curriculum and the environment around the students. In addition, teachers also act as a liaison between concepts and reality, inviting students to discuss and make direct observations after watching the video. In classroom management, teachers create an interactive learning atmosphere by encouraging discussion and collaboration between students. With this role, learning becomes more effective and meaningful.